HIF-1α facilitates glioma proliferation and invasion by activating pyroptosis signaling axis - Xin-Wei Wang; Hao Fu; Ya-Min Zhang (Chinese Neurosurgical Journal, 2024)
Abstract Background HIF-1α is thought to be a novel regulator which contributes to carcinogenesis. However, the mechanism underlying the effect of HIF-1α in gliomas remains largely unknown. Methods In the research, we demonstrate that HIF-lα mRNA and protein levels are elevated in glioma cells. The colony formation assays, transwell assays, and wound-healing assays showed that overexpression of HIF-1α promoted proliferation and invasion of glioma cells. Results Overexpression of HIF-lα also increased the expression of inflammatory factors related to pyrolysis (TNF-α, IL-10, and IL-1β) and protein related to pyrolysis signal pathway (NLRP3, ASC, caspase-1, GSDMD, and GSDME). Conclusions Therefore, we speculate that HIF-1α promotes the proliferation and invasion of glial cells by regulating pyrolysis pathway. These results might provide a novel strategy and target for treatment of glioma.